Long-term real-life efficacy and safety of infliximab and adalimumab in the treatment of inflammatory bowel diseases outpatients. Issue 5 (19th March 2021) - Tursi, Antonio; Mocci, Giammarco; Lorenzetti, Roberto; Allegretta, Leonardo; Brandimarte, Giovanni; Cassieri, Claudio; Colucci, Raffaele; De Medici, Antonio; Faggiani, Roberto; Ferronato, Antonio; Fiorella, Serafina; Forti, Giacomo; et al.
Abstract : Background: Infliximab and adalimumab are widely used for the treatment of Crohn's disease and ulcerative colitis. Aim: To compare the long-term efficacy and safety of infliximab and adalimumab in a large cohort of Crohn's disease and ulcerative colitis patients reflecting real-life clinical practice. Methods: Seven hundred twelve patients were retrospectively reviewed, 410 with Crohn's disease (268 treated with adalimumab and 142 with infliximab; median follow-up 60 months, range, 36–72) and 302 with ulcerative colitis (118 treated with adalimumab and 184 with infliximab; median follow-up 48 months, range, 36–84). Results: In Crohn's disease, clinical remission was maintained in 75.0% of adalimumab vs. in 72.5% of infliximab patients ( P = 0.699); mucosal healing and steroid-free remission were maintained in 49.5% of adalimumab vs. 63.9% of infliximab patients ( P = 0.077) and in 77.7% of adalimumab vs. 77.3% in infliximab group ( P = 0.957), respectively. In ulcerative colitis, clinical remission was maintained in 50.0% of adalimumab vs. 65.8% of infliximab patients ( P < 0.000); mucosal healing and steroid-free remission were maintained in 80.6% of adalimumab vs. 77.0% of infliximab patients ( P = 0.494) and in 90.2% of adalimumab vs. 87.5% of infliximab patients ( P = 0.662), respectively. At the multivariate analysis, ileocolonic location and simple endoscopic score for Crohn's disease >10 were predictors of failure in Crohn's disease; treatment with adalimumab, BMI ≥30 and Mayo score >10 were predictors of failure in ulcerative colitis. infliximab was more likely to cause adverse events than adalimumab (16.6 vs. 6.2%, P < 0.000). Conclusion: Both adalimumab and infliximab are effective in long-term outpatients management of inflammatory bowel diseases. Adalimumab had a lower rate of adverse events.